Probing the limits of Figures and Grounds: Artificial Intelligence and Quantum Computation - Gustafson, Erik (New Explorations)

(untitled) (New Explorations Association, 2024)
The present article employed McLuhan’s figure/ground distinction to probe the boundaries of artificial intelligence (AI) and computation. In popularizing the intellectual tradition of media ecology, Marshall McLuhan warned scholars that confusing the figure (i.e. the content or software) with the ground (i.e. the medium of communication or hardware) would lead to inadequate and incorrect analyses and appraisals of the effects of our media technologies. However, the present article contends that scholars of all stripes are at risk of falling prey to that exact mistake with regards to AI. The present article argues that AI, though having appeared as a touchstone issue in media and communication studies recently, represents the figure, whereas the computational hardware is the ground. Moreover, with continued development of quantum computation technologies, the ground upon which our AI programs rest is in the infantile stages of undergoing a revolutionary change. In sum, this article probes the significance of AI and Quantum computation for the coming decades.